MitraClip for the treatment of heart failure with mitral regurgitation: A cost-effectiveness analysis in a Chinese setting - Xia, Wengang; Han, Kangning; Lou, Yake (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure with mitral regurgitation is associated with decreased survival. Guideline-directed medical therapy and transcatheter edge-to-edge repair (TEER) are the main options for HF patients with severe mitral regurgitation who are considered high-risk or prohibitive. There is no study investigating the cost-effectiveness of MitraClip versus optimal medical therapy in China setting. Methods: A combined decision tree and Markov model were developed to compare the cost-effectiveness MitraClip versus optimal medical therapy with a lifetime simulation. The primary outcome was the incremental cost-effectiveness ratio (ICER), which represented incremental costs per quality-adjusted life-year (QALY). The willingness-to-pay (WTP) threshold was set three times of per capita GDP in China in 2021, which was 242,928 CNY. MitraClip would be considered cost-effective if the ICER obtained was lower than the WTP threshold, otherwise, it would be thought not cost-effective. One-way sensitivity and probabilistic sensitivity analysis were performed to validate the robustness of the results. Results: After a simulation of lifetime, the overall cost for a patient in MitraClip cohort was 423,817 CNY, and the lifetime cost in OMT was 28,369 CNY. The corresponding effectiveness in both cohorts were 2.32 QALY and 1.80 QALY per person, seperately. The incremental cost and increment effectiveness was 395,448 CNY and 0.52 QALY, the ICER was 754,410 CNY/QALY. The ICER obtained was higher than the WTP threshold. Sensitivity analysis validated our finding. Conclusion: MitraClip resulted in more effectiveness but with more cost compared with optimal medical therapy, and the incremental cost-effectiveness ratio obtained was higher than the willingness-to-pay threshold. MitraClip is considered not cost-effective in Chinese heart failure patients with secondary mitral regurgitation.